Developing a water-energy-food nexus-based approach for sustainable climate change adaptation interventions : a case study of Mpumalanga province - Ramoelo, Abel (University of Pretoria, 2024)
Dissertation (MSc (Geoinformatics))--University of Pretoria, 2023.